Ability of an Appointment Complexity Categorization System Applied by Non-Medical Personnel to Discriminate Between Patient Categories - Brain, Charity; Allison, Lauren; Fernandez, Candace; Kreisler, Rachael (Journal of Student-Run Clinics, 2020)
Background: The Midwestern University College of Veterinary Medicine hosts student-run free clinics through the campus-wide interprofessional program, Health Outreach through Medicine and Education. Veterinary students, attending veterinarians, and non-medical volunteers conduct clinics on a first-come-first-served basis. Patients are declined once estimated capacity is reached. Historically, capacity was based on the number of patients, but clinic end-time was found to be highly variable. An appointment complexity categorization system based on presenting complaint (used as a proxy for appointment duration) was implemented in an attempt to maximize patients seen while allowing for an on-time clinic conclusion. Methods: A rubric was constructed based on prior clinical experience and provided to non-medical personnel assisting with check-in to determine a point value (1-3) for each patient, with lower point value appointments being simpler, and higher point appointments being more complex. Clinic capacity was set at 24 points. Appointment duration for each point category was analyzed via Kruskal-Wallis equality of populations rank test and Dunn’s test of multiple comparisons. Results: Median duration was the same for 1- and 2-point appointments (24 minutes), but longer for 3-point appointments (62 minutes). Duration of 3-point appointments was significantly different than 1-point (p=0.0071) and 2-point (p=0.0201) appointments, while duration between 1- and 2-point appointments was not different. Conclusions: Non-medical personnel using a rubric were able to discriminate between simple (1-point) and complex (3-point) appointments but were unable to discriminate between simple and complicated (2-point) appointments. However, this utility of this in clinical practice was minimal.